In situ investigation of stress-induced martensitic transformation in granular shape memory ceramic packings. (15th April 2019) - Rauch, Hunter A.; Chen, Yan; An, Ke; Yu, Hang Z.
Abstract: Stress-induced martensitic transformation can occur in granular shape memory materials when individual particles experience high stresses and transform from a high-symmetry austenite phase to a low-symmetry martensite phase. This involves a highly heterogeneous distribution of the driving force and very low mechanical constraint for martensite nucleation, so the transformation behavior can be dramatically different from the well-documented case of monolithic solids. In this work, we investigate the stress-induced martensitic transformation in granular shape memory ceramic packings, which consist of single-crystal micro-particles of ZrO2 -12 at%CeO2 and ZrO2 -15 at%CeO2 . Through in situ neutron diffraction, we study how the phase fraction, lattice strain, and integral peak broadness evolve during external loading, unloading, and subsequent heating. Several peculiar features are discovered, including (i) a continuous mode of transformation with a wide range of transformation loads, (ii) co-evolution of the packing structure, contact deformation, and martensitic transformation, and (iii) a strong correlation between the peak broadening and the transformed phase fraction. In addition, we show the first direct evidence of reversible stress-induced martensitic transformation in granular materials. We finally discuss the mechanism for martensite nucleation and growth in granular packings and show how that leads to the observed transformation characteristics. Graphical abstract: Image 1